Making, Multi-Vocality and Experimental Archaeology: The Pallasboy Project - Benjamin Gearey; Mark Griffiths; Brian Mac Domhnaill; Cathy Moore; Orla-Peach Power (EXARC Journal)
This paper outlines The Pallasboy Project, which set out to craft a replica of the eponymous Irish Iron Age wooden vessel. We consider the process and progress of the project, as it developed in a number of slightly unusual directions. The paper includes a description of the experimental work, alongside personal reflections and comments by the people who became involved in the project as it progressed. The work was documented visually through photography, video and artistic responses and selections from this material are included. Unconventional (in experimental archaeological terms) ‘interactions’ are outlined, including a performance by musicians who ‘played’ the replica vessel. This paper is also intended as a guide to the project blog, which hosts the written pieces and other content linked to below. The project subsequently moved onto consider other wooden archaeological artefacts, also discussed on the blog, but in this paper we focus on the Pallasboy Vessel itself. The ethos embodied by the approach can be conceived as one of ‘multi-vocal understandings’, a concept inspired by the process known as ‘Deep Mapping’. Springett (2015, p.628) has described this as an approach through which: “There is no privileging or authorizing knowledge of one source of information over another and all agents have equal resonance ... at least philosophically.” In other words, the practical, experimental archaeological crafting is just one of the various different strands and ‘responses’ to ‘understanding’ the Pallasboy vessel as an Iron Age artefact, but also the replica as very much a contemporary object. We discuss how concepts of ‘multivocality’ may be of broader value for experimental archaeology.